Dehydroascorbic acid quantification in human plasma: Simultaneous direct measurement of the ascorbic acid/dehydroascorbic acid couple by UPLC/MS-MS - Violet, P.-C.; Munyan, N.; Luecke, H.F.; Wang, Y.; Lloyd, J.; Patra, K.; Blakeslee, K.; Ebenuwa, I.C.; Levine, M. (Redox biology, 2024)
Ascorbic acid (AA, vitamin C) and dehydroascorbic acid (DHA) constitute a biological couple. No technique can accurately, independently, and simultaneously quantify both members of the couple in animal and human samples, thereby constraining advances in physiology and pathophysiology. Here we describe a new UPLC/MS/MS method to measure both compounds directly and independently in human plasma. Lower limits of quantification were 16 nM, with linear coefficients >0.99 over a 100-fold concentration range. The method was stable and reproducible with <10 % injection-to-injection variation. Use of isotopic labeled internal standards for both compounds ensured precision and accuracy. Plasma preparation required only 2 steps. In plasma samples from 14 anonymized subjects who met criteria for blood donation, mean concentrations were 6±2 μmol/L (mean ± SD) and 56 ± 14 μmol/L for DHA and AA respectively, with (DHA)/(AA + DHA) ratio of 9.8 %. This method represents a pioneering approach to measuring the AA/DHA couple in human plasma. •Novel LC-MS method for quantifying dehydroascorbic acid in human plasma.•Simultaneous, direct, and independent quantification of AA/DHA redox couple.•Streamlined 2-step sample preparation.•Lower quantification limit 16 nM; linear co-efficient >0.99 over 100-fold concentration range.•Enhanced sensitivity and specificity using 13C internal standards.